2019
DOI: 10.3390/insects10100339
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regulatory Host Genes Involved in Sigma Virus Replication Using RNAi Knockdown in Drosophila

Abstract: The Drosophila melanogaster sigma virus, a member of the Rhabdoviridae family, specifically propagates itself in D. melanogaster. It contains six genes in the order of 3′-N–P–X–M–G–L-5′. The sigma virus is the only arthropod-specific virus of the Rhabdoviridae family. Sigma-virus-infected Drosophila may suffer from irreversible paralysis when exposed to a high CO2 concentration, but generally, no other symptoms are reported. A recent study reported that host gene expression in immune pathways was not changed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A considerable number of AMP genes have been identified in Drosophila , the honey bee Apis cerana and the silkworm Bombyx mori ( 18 20 ). However, two antiviral screening experiments failed to show that AMPs are a class of antiviral factors in Drosophila ( 21 , 22 ). Intriguingly, other data in the literature have indicated that AMPs have antiviral function in Drosophila and B. mori ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable number of AMP genes have been identified in Drosophila , the honey bee Apis cerana and the silkworm Bombyx mori ( 18 20 ). However, two antiviral screening experiments failed to show that AMPs are a class of antiviral factors in Drosophila ( 21 , 22 ). Intriguingly, other data in the literature have indicated that AMPs have antiviral function in Drosophila and B. mori ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also reported no differentially expressed immune genes in response to DMelSV [ 134 ]. However, another study found an increase in DMelSV replication in PGRP-LC and domeless knockout flies, suggesting the recruitment of IMD and JAK/STAT pathways respectively in DMelSV infection [ 135 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, ablation of these PLINs causes significant increases in VLDL secretion [ 33 ] to improve hepatic steatosis [ 33 , 34 , 35 ]. PLIN5 is another LD family of protein that is highly expressed in oxidative tissues including liver [ 36 ]. Trevino et al reported that a rise of PLIN5 in the liver drives lipid accumulation [ 37 ] by impairing lipolysis through its interaction with lipolysis regulatory proteins [ 38 ].…”
Section: Discussionmentioning
confidence: 99%